Inovasi Program Pendaftaran Tanah Sistematis Lengkap (Ptsl) Pada Kantor Badan Pertanahan Nasional Kota Surabaya I - Ismail Ismail; Fierda Nurany; Dhellia Febby Paquita (FISIP UWP, 2024)
Government innovations are needed by the community over time, one of which is the Complete Certificate Land Registration Program Innovation in Surabaya. In this case the process of implementing land registration which is a series of activities implemented by the government on an ongoing, regular and continuous basis and includes a collection, processing of manuscripts and also presenting and maintaining physical data and also juridical data in the form of maps and lists, relating to the field of -Plots of land and apartment units, including the provision of evidence as a right to land parcels that already have authority and have ownership rights to apartment units and certain other rights that burden them. The benefits in this case that are sustainable in discussions regarding the implementation of land registration can provide legal certainty and legal protection to rights holders over a parcel of land, an apartment and other rights that are registered so that they can easily have evidence against the public that it owns a land certificate which is the holder of the rights in question and provides a relief to other parties so that they can apply for land registration on their own rights